2019
DOI: 10.1186/s13104-019-4459-x
|View full text |Cite
|
Sign up to set email alerts
|

Premarital sexual practice and associated factors among adolescents in the refugee camps in Tigray, northern Ethiopia

Abstract: Objective Premarital sexual practice during adolescence time may lead to different sexual and reproductive health problems including HIV/AIDS. This study was aimed to assess the prevalence of premarital sexual practice and associated factors among adolescents living in the refugee camps in Tigray, northern Ethiopia. Result The prevalence of premarital sexual practice was 47.6% [95% CI (43.3%, 51.9%)]. The age (mean ± SD) of the study participants was 17.4 ± 2.71 (15–24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This trend is also seen in other countries too, even though at a much higher rate (7). Premarital sexual practice among youths is higher in Ethiopia (47.6%) (8), China (22.4%) and Taiwan (22%) (9).…”
Section: Introductionmentioning
confidence: 56%
“…This trend is also seen in other countries too, even though at a much higher rate (7). Premarital sexual practice among youths is higher in Ethiopia (47.6%) (8), China (22.4%) and Taiwan (22%) (9).…”
Section: Introductionmentioning
confidence: 56%
“…A total of thirty-two cross-sectional studies involving 18, 354 study subjects were included to estimate the pooled prevalence of premarital sexual practice and its association with peer pressure and watching pornography among young individuals in Ethiopia. Regarding the geographic area, thirteen studies were from Oromia region 14 , 26 , 29 , 34 , 38 , 40 43 , 45 , 47 , 51 , 52 , seven studies were from Amhara region 25 , 32 , 33 , 35 – 37 , 50 , five studies were from Tigray region 13 , 27 , 48 , 49 , 53 , six studies were from SNNPR 5 , 28 , 30 , 39 , 44 , 46 and the rest one study was from Addis Ababa, capital city of Ethiopia 31 . The sample size ranged from 230 students among a study done in Alamata, Tigray region 27 to 2,766 students among a study done in Eastern Ethiopia, Oromia region 38 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the included articles, 41.6% of the included studies were conducted from Oromia region [5,11,18,24,29,33,35,[37][38][39]: seven studies from Amhara region [19-22, 28, 30, 34]: four studies were reported from SNNPR [9,26,27,32]: two articles in Tigray [23,25] and one articles [31] conducted in Addis Ababa city administration. Except one study which was conducted at community level in Tigray region [23], all other studies were done at the institutional level. After critical appraisal of each articles based on Newcastle-Ottawa quality assessment scale, both in peer and independently, each studies scored in the range of 6up to 9 values.…”
Section: Resultsmentioning
confidence: 99%